Peningkatan Daya Mampu Dan Efisiensi PLTG Tipe ABB 13E2 Melalui Optimalisasi Sudut VIGV - Sahlan Sahlan; Erlina Erlina; Ronny Koeshartarto (JURNAL POWERPLANT, 2014)
Gilimanuk power plant (ABB 13E2) with an installed capacity of 133.8 MW generating units that have a strategic role in the Bali Sub Systems (± 25 % when the Peak Load) . A decrease in power capable , increased heat rate , especially when approaching the maintenance period , becomes a problem that impact on the efficiency of the unit . Departing from the problem arose the idea that by optimizing the angle openings VIGV (Variable Inlet Guide Vane) but remains within safe limits with the aim of improving the performance and efficiency of the generating units. After optimization of the opening angle of VIGV gained increased power capable of 2-3 MW units , an increase of 0.2 % efficiency units and no adverse effect on the material and exhaust emissions after the NDT test in 2012 Major Inspection and monitoring of emissions via CEMS .